Transformation of street-style fried rice into star-hotel cuisine: Innovations in processing, safety, sensory quality, and culinary tourism positioning - I Wayan Andika Saputra; Cokorda Gede Putra Yudistira; Kasiani Kasiani; Majid Wajdi; Ratna Dewi; Muhammad Ahmad Mazher; Auwal Ahmed Ibrahim; Chet Narayan Acharya (Yayasan Mitra Persada Nusantara, 2026)
This study explores how humble street-style fried rice can be transformed into a premium star-hotel dish by integrating advances in food processing, quality control, and culinary tourism strategy. The aims are to enhance safety and shelf-life, standardize sensory quality, and reposition fried rice as a signature upscale offering. Methodologically, the paper synthesizes recent developments in prepared fried rice technologies, including novel thermal and non-thermal processing, freezing, and quality-monitoring tools, alongside case-based insights from tourism-driven dish upgrading and local rice innovations as culinary icons. Analysis focuses on microbial safety, starch retrogradation, texture, colour, and flavour stabilization, as well as menu standardization, presentation, and branding for tourist and hotel markets. The study concludes that combining advanced processing (e.g., physical field and static magnetic field freezing) with standardized recipes and tourism-oriented branding can elevate fried rice from roadside fare to a consistent, marketable star-hotel dish.